Spin Hall angle of rhodium and its effects on magnetic damping of Ni₈₀Fe₂₀ in Rh/Ni₈₀Fe₂₀ bilayer - Mahato, Bipul Kr. (2023)
We report the investigation of the spin Hall angle (SHA) of Rhodium (Rh) and the effective magnetic damping constant of Ni80Fe20 in Rh (10 nm)/Ni80Fe20 (10 nm) bilayer system using Spin Torque Ferromagnetic Resonance (STFMR) spectroscopy and density functional theory based analysis. The filtered DC output voltages from Rh (10 nm)/Ni80Fe20 (10 nm) bilayer system at different input signal frequencies and powers for a complete 360º angle were measured. The average magnetic damping constant of Ni80Fe20 is found to be 0.017 and the angle-dependent study shows a 2-fold symmetry with the in-plane anisotropy field of 120 Oe. The SHA of Rh is found to be 0.2 %. The results agrees well with the calculations based on density functional theory where we found spin Hall conductivity ( ) at the charge-neutral Fermi level (EF) is positive and it’s magnitude is ~423 (ℏ ) (S/cm).